Ecohydrology and stewardship of Alberta springs ecosystems. Issue 5 (30th January 2015) - Springer, Abraham E.; Stevens, Lawrence E.; Ledbetter, Jeri D.; Schaller, Elizabeth M.; Gill, Karen M.; Rood, Stewart B.; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract We studied the role of ecological and anthropogenic impact gradients on ecosystem structure and composition of 56 freshwater springs among mountain, foothills, and prairie ecoregions in southern Alberta, Canada. A random stratified site selection from 2008 to 2012 was based on representation of characteristic springs types across elevation, ecoregions, and land use histories. Springs emergence varied over geomorphic contexts and was dominated by hillslope (28), helocrene (marsh, 13), and rheocrene (stream channel, seven) types, with fewer limnocrene (pool, four), cave (two), gushet (one), and hanging garden (one) springs. Among these springs, specific conductance of non‐geothermal springs water was negatively related to elevation and groundwater temperature (R2 = 0.343 and 0.336 respectively). Plant species richness was positively related to habitat area (R2 = 0.328) and weakly to geomorphic diversity (R2 = 0.135) and total alkalinity and specific conductance (R2 < 0.181). We detected at least 444 higher native plant taxa on only 3.82 ha of springs habitat, equalling 25% of Alberta's flora on <0.001% of the provincial land area. Non‐native plant species density was positively related to that of native plants (R2 = 0.36). Human impacts on springs included livestock production and domestic water supplies, while beaver and other wildlife commonly influenced ecosystem function on protected lands. We conclude that the springs of Alberta are ecologically important but are understudied and inadequately protected, especially with increasing demand for groundwater as a result of extensive allocation and use of surface water in southern Alberta. Copyright © 2014 John Wiley & Sons, Ltd.